Nickel-iron bimetal organic polymer, preparation method thereof and application of nickel-iron bimetal organic polymer in urea electrosynthesis
Through the nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe, the problems of high energy consumption and greenhouse gas emissions in the traditional urea synthesis industry are solved, and the efficient and selective urea electrosynthesis is achieved, with good industrial application prospects.
Patent Information
- Application Number
- CN202411958194.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The traditional urea synthesis industry relies on high-energy-consuming ammonia synthesis processes, which produces a large amount of greenhouse gases and three wastes. The performance and economics of the electrocatalysts are insufficient, which limits the industrial application of electrosynthetic urea.
Ni-PMDA@Fe is used to synthesize the nickel-iron bimetallic organic polymer catalyst by solvothermal strategy and stirring diffusion method, and is used for urea electrosynthesis to improve catalytic efficiency and selectivity.
At -0.5V vs. RHE, the catalyst achieved a urea yield of 409.57 mg·h-1·g-1 and a Faraday efficiency of 41.06%, which was better than the previously prepared Ni-BDC catalyst and Ni-PMDA precursor catalyst, and effectively inhibited the formation of by-product ammonia nitrogen.
Smart Images

Figure CN119751911A_ABST
Abstract
Description
Technical Field
[0001] The patent of this invention belongs to the field of electrocatalysis, and relates to a nickel-iron bimetallic organic polymer, a preparation method thereof, and an application in urea electrosynthesis. Background Art
[0002] Urea is a small molecule compound that plays an important role in the national economy. It is an important agricultural fertilizer and industrial raw material, and is related to national food security and the process of human industrialization. The traditional urea synthesis industry uses syngas reforming and is heavily dependent on the energy-intensive synthetic ammonia HaberBosch industry (>2% of the global energy supply). my country's urea production generally uses coal-to-urea process, which produces a large amount of three wastes (waste liquid, waste gas, solid waste) during the reaction process, and produces a large amount of greenhouse gases. In view of the various drawbacks of traditional industrial methods, the electrosynthesis strategy for synthesizing urea has become a hot topic in recent years. The use of electrochemical reaction to produce urea in one-step CN coupling reaction can not only use CO2 and nitrogen oxide waste to synthesize industrial products, but also is a feasible means to solve the greenhouse effect and nitrogen-containing waste pollution. The key to electrosynthesis is to find electrocatalysts with excellent performance and economical availability. Compared with traditional precious metal catalysts, transition metal catalysts have large reserves of raw materials and good preparation economy, and have significant advantages in industrial applications; compared with single-atom catalysts, bimetallic catalyst systems can provide multiple active sites, play a synergistic role, and change the coordination environment. The bimetallic system of nickel and iron is a widely studied bitransition metal system. Polymer catalysts formed by metals and organic ligands are often used to catalyze electrochemical reactions. Pyromellitic dianhydride (PMDA) is an excellent tetracarboxylic acid organic ligand. Bimetallic catalysts and coordination polymer theory provide theoretical feasibility for urea electrosynthesis. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe with readily available raw materials, a simple preparation method, high catalytic efficiency and good selectivity, and its application in urea electrosynthesis.
[0004] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a nickel-iron bimetallic organic polymer, which uses Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and pyromellitic anhydride PMDA as raw materials, wherein Ni(NO3)3·6H2O and Fe(NO3)3·9H2O provide metal atoms, PMDA serves as anhydride ligand, and tetrahydrofuran THF and anhydrous ethanol are solvents.
[0005] The above-mentioned nickel-iron bimetallic organic polymer uses phthalic acid BDC to replace pyromellitic dianhydride PMDA.
[0006] The preparation method of the above-mentioned nickel-iron bimetallic organic polymer is as follows:
[0007] 1) Ni(NO3)2·6H2O solid and PMDA solid are dissolved in THF respectively to obtain a metal salt solution and a PMDA dispersion, the PMDA dispersion is added dropwise to the metal salt solution, the mixed solution is dispersed by ultrasound, transferred to a Teflon high-pressure reactor, placed in a blast drying oven for reaction for a specific time and cooled to room temperature, the reaction solution is filtered and the obtained solid is dried and ground to obtain a Ni-PMDA precursor;
[0008] 2) Take Ni-PMDA precursor and Fe(NO3)3·9H2O solid, add anhydrous ethanol, stir for 12 hours to allow iron and Ni-PMDA precursor to form a polymer, transfer the stirred liquid to a centrifuge tube for centrifugation, repeat the centrifugation several times and wash, and transfer to a vacuum dryer to obtain Ni-PMDA@Fe solid.
[0009] In the above-mentioned method for preparing a nickel-iron bimetallic organic polymer, in step 1), the molar ratio of Ni(NO3)2·6H2O solid to PMDA is 5:2.
[0010] In the above-mentioned method for preparing a nickel-iron bimetallic organic polymer, in step 1), the reaction temperature is 120° C., the reaction time is 48 hours, and the reaction is naturally cooled to room temperature.
[0011] In the above-mentioned method for preparing a nickel-iron bimetallic organic polymer, in step 3), the mass ratio of Ni-PMDA precursor:Fe(NO3)3·9H2O=1:1.
[0012] A nickel-iron bimetallic organic polymer catalytic electrode is prepared by mixing the nickel-iron bimetallic organic polymer with acetylene black, DuPont membrane solution, isopropanol and ultrapure water to form ink, and dripping the ink onto a carbon cloth using a syringe to obtain a catalytic electrode.
[0013] The above-mentioned nickel-iron bimetallic organic polymer catalytic electrode, nickel-iron bimetallic organic polymer: acetylene black: DuPont membrane solution: isopropanol: ultrapure water = 3mg: 3mg: 30ul: 170ul: 200ul.
[0014] The application of the above nickel-iron bimetallic organic polymer catalytic electrode in electrochemical urea synthesis.
[0015] In the above application, the above-mentioned nickel-iron bimetallic organic polymer catalytic electrode is used as the working electrode, the counter electrode is a platinum sheet electrode, the reference electrode uses an Ag / AgCl reference electrode, the cathode electrolyte is 35 ml each of 0.1M KNO3 solution and 0.1M KHCO3 solution, the anolyte uses 70 ml of 0.1M KHCO3 solution, the electrolysis time is 2 hours at a single potential, and the cathode electrolyte product is collected.
[0016] The beneficial effects of the present invention are:
[0017] 1. The present invention uses Ni(NO3)2·6H2O and Fe(NO3)3·9H2O as reaction raw materials, and uses a solvent thermal strategy and a stirring diffusion method to synthesize a bimetallic polymer. The reaction substrate is economical and easy to obtain, the reaction conditions are mild and controllable, and the synthesis strategy is easy to operate.
[0018] 2. The catalytic electrode synthesized by the present invention catalyzes the electrosynthesis of urea, reaching a maximum of 409.57 mg·h at -0.5 V vs. RHE. -1 ·g -1 The urea yield and Faradaic efficiency of 41.06% were better than those of the previously prepared Ni-BDC catalyst and Ni-PMDA precursor catalyst, indicating the excellent catalytic activity of the bimetallic catalyst.
[0019] 3. The catalyst of the present invention has a good inhibitory effect on the main by-product ammonia nitrogen. The ammonia nitrogen concentration measured at -0.3V vs.RHE to -0.05V vs.RHE is lower than 53mg·h -1 ·g -1 , indicating the excellent electrocatalytic selectivity of the catalyst of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the synthesis of the carbon cloth-supported nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe prepared in Example 1.
[0021] Figure 2 This is the Fourier transform infrared spectrum (FT-IR) of the carbon cloth-supported nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe prepared in Example 1.
[0022] Figure 3 This is the powder X-ray diffraction (XRD) pattern of the carbon cloth-supported nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe prepared in Example 1.
[0023] Figure 4 This is a scanning electron microscope (SEM) image of the carbon cloth-supported nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe prepared in Example 1.
[0024] Figure 5 This is a diagram of the electrochemical experimental device of the carbon cloth-loaded Ni-PMDA@Fe catalytic electrode in Example 2.
[0025] Figure 6This is the linear voltammetric curve (LSV) diagram of the carbon cloth-supported Ni-PMDA@Fe catalytic electrode in Ar and CO2 atmosphere in Example 2 (left) and the LSV curve comparison diagram of the three catalysts Ni-PMDA@Fe, Ni-PMDA, and Ni-BDC (right).
[0026] Figure 7 This is the urea yield diagram of the carbon cloth-loaded Ni-PMDA@Fe catalytic electrode in Example 2 (left) and the yield comparison diagram of Ni-PMDA@Fe, Ni-PMDA, Ni-BDC and empty carbon cloth (right).
[0027] Figure 8 This is the urea Faraday efficiency diagram of the carbon cloth-supported Ni-PMDA@Fe catalytic electrode in Example 2 (left) and the selectivity comparison diagram of Ni-PMDA@Fe, Ni-PMDA, and Ni-BDC (right).
[0028] Fig. 9 This is a comparison chart of the double-layer capacitance of the Ni-PMDA@Fe catalyst of the present invention and Ni-PMDA, Ni-BDC, and empty carbon cloth in Example 2. DETAILED DESCRIPTION
[0029] Example 1 Preparation of Carbon Cloth-Loaded Nickel-Iron Bimetallic Organic Polymer Ni-PMDA@Fe Electrode
[0030] (I) Preparation method
[0031] 1) Preparation of Ni-PMDA polymer precursor: Use a precision electronic balance to accurately weigh 1.5mmol of reactant Ni(NO3)2·6H2O and 0.6mmol of PMDA ligand, dissolve Ni(NO3)2·6H2O and PMDA in 30ml and 15ml of THF, respectively, stir for 30min to form a uniform metal salt solution and PMDA dispersion, then use a rubber dropper to drop the PMDA dispersion into the metal salt solution drop by drop, and use a magnetic stirrer to stir continuously during the addition process. The mixed solution is ultrasonically dispersed, transferred to a 100ml Teflon autoclave, reacted at 120℃ in a forced air drying oven for 2880min, cooled naturally to room temperature, the liquid in the reactor is taken out, and the liquid in the reactor is filtered using a sand core filter device, and the solid particles on the filter paper layer are transferred to a vacuum drying oven, vacuum dried for 12h to obtain Ni-PMDA precursor.
[0032] 2) Synthesis of Ni-PMDA@Fe polymer: Use a precision electronic balance to accurately weigh 50 mg of Ni-PMDA precursor and 50 mg of Fe(NO3)3·9H2O solid, add 50 ml of anhydrous ethanol, and use a magnetic stirrer to stir for 12 hours to allow iron and the precursor to form a polymer. Transfer the stirred liquid to a centrifuge tube, centrifuge at 12,000 rpm for 10 minutes, repeat the centrifugation three times and wash with anhydrous ethanol three times, transfer the solid in the centrifuge tube to a vacuum dryer for 12 hours to obtain Ni-PMDA@Fe solid.
[0033] 3) Pretreatment of carbon cloth: Cut the conductive carbon cloth into regular rectangles of 1 cm × 2 cm, and soak them in acetone, anhydrous ethanol, concentrated nitric acid, anhydrous ethanol, and acetone in sequence for pretreatment. Each soaking is ultrasonically oscillated for 30 minutes, and repeatedly washed with ultrapure water. The pretreated carbon cloth is placed in a vacuum drying oven and dried for later use.
[0034] 4) Preparation of Ni-PMDA@Fe polymer catalytic electrode: Use an electronic balance to accurately weigh 3mg Ni-PMDA@Fe catalyst powder, 3mg acetylene black, use a pipette to accurately absorb 30ul DuPont membrane solution, 170ul isopropanol, and 200ul ultrapure water, mix and ultrasonically disperse for 30min to make ink. Use a syringe to evenly drop the catalyst ink on the treated carbon cloth, with 10-12 drops per piece, and weigh after drying. Calculate the catalyst loading based on the mass of the carbon cloth before and after the addition.
[0035] (II) Test results
[0036] Figure 1 This is the preparation route of the carbon cloth-supported nickel-iron bimetallic organic polymer Ni-PMDA@Fe electrode in Example 1, which can be divided into three parts: synthesis of Ni-PMDA precursor, synthesis of Ni-PMDA@Fe polymer and preparation of catalyst electrode. Figure 2 The Fourier transform infrared (FT-IR) spectra of polymer Ni-PMDA@Fe and PMND ligands show obvious conjugated anhydride features, including the -1 The strong absorption peak of C=O at 1200cm -1 ~1310cm -1 The cyclic anhydride CO stretching vibration at 3400 cm -1 The broad and strong peak at 1400 cm-1 is caused by the -OH stretching vibration of the exposed carboxylic acid in the polymer. -1 and 1550cm -1 The two continuous strong peaks appearing at are consistent with the characteristic peaks of carbonyl in carboxylate, indicating that the metal and PMDA ligands are successfully coordinated and polymerized. Figure 3This is a scanning electron microscope (SEM) image of the polymer Ni-PMDA@Fe. The polymer powder appears as an irregular block solid at the micron level with a rough surface morphology and some crack defects. Figure 4 This is the powder X-ray diffraction (XRD) spectrum of the polymer Ni-PMDA@Fe. The Ni-PMDA precursor has a similar peak position to the previously reported Co-PMDA and is considered to be a homologue. Ni-PMDA@Fe shows a large carbon bulge peak and low crystallinity, showing typical low-crystalline polymer characteristics.
[0037] Comparative Example 1 Ni-BDC Catalyst
[0038] Preparation of Ni-BDC catalyst: Use a precision electronic balance to accurately weigh 1.5mmol of reactant Ni(NO3)2·6H2O and 0.6mmol of terephthalic acid BDC ligand, dissolve Ni(NO3)2·6H2O and BDC in 30ml and 15ml of THF respectively, stir for 30min to form a uniform metal salt solution and BDC dispersion, then use a rubber dropper to drop the BDC dispersion into the metal salt solution drop by drop, and use a magnetic stirrer to stir continuously during the addition process. The mixed solution is ultrasonically dispersed, transferred to a 100ml Teflon autoclave, reacted at 120℃ in a blast drying oven for 2880min, cooled naturally to room temperature, took out the liquid in the reactor, filtered the liquid in the reactor using a sand core filter, transferred the solid particles on the filter paper layer to a vacuum drying oven, and vacuum dried for 12h to obtain the Ni-BDC catalyst.
[0039] Example 2 Application of Ni-PMDA@Fe electrode in electrocatalytic urea synthesis
[0040] (I) Test method
[0041] The experimental setup of this experiment is as follows Figure 5The experimental electrolyzer uses the H-type electrolytic cell of Tianjin Aida, with a single cell volume of 100ml, and the proton exchange membrane uses the Nafion117 membrane of DuPont. The Ni-PMDA@Fe catalytic electrode prepared in Example 1 is fixed to the cathode electrode clamp as the working electrode, the reference electrode uses the Ag / AgCl electrode, the counter electrode uses the platinum electrode, the cathode electrolyte uses 35ml 0.1M KNO3 solution and 35ml 0.1M KHCO3 mixed electrolyte, and the anolyte is 70ml 0.1M KHCO3 electrolyte. Before the test, the electrode needs to be pretreated by CV activation for 2000s, followed by LSV linear voltammetry test, constant voltage electrolysis (it) test, and electrochemical active surface area (ECSA) test. The it potential is set to -0.3~0.5Vv.s.RHE, and the electrolysis time is set to 2h. The components of the electrolyte were detected by spectrophotometry using the external standard method. The urea concentration in the electrolyte was detected by the diacetyl monooxime method, and the ammonia nitrogen concentration in the electrolyte was detected by the indophenol blue method.
[0042] (II) Test results
[0043] Using Ni-PMDA@Fe electrode as the working electrode, linear voltammetry tests were carried out in CO2 and Ar atmospheres, and the corresponding linear voltammetry curves (LSV) were plotted. Figure 6 This is the LSV curve measured experimentally. According to the test results, the current density of the Ni-PMDA@Fe catalyst in CO2 atmosphere is higher than that in Ar atmosphere, indicating that the catalyst has CN coupling catalytic activity. In addition, the LSV of Ni-PMDA@Fe is compared with that of the precursor Ni-PMDA and Ni-BDC catalysts. Among them, the Ni-PMDA@Fe catalyst has the highest current density in the range above -0.3Vvs.RHE, indicating the activity advantage of the catalyst of the present invention. Figure 7 The yield of the target product urea was measured by the diacetyl monooxime method and the urea yield of Ni-PMDA@Fe catalyst was compared with that of Ni-PMDA catalyst, Ni-BDC catalyst and blank carbon cloth. The catalyst of the present invention reached a maximum of 409.57 mg·h at -0.5 V vs. RHE. -1 ·g -1 The yield was higher than that of blank carbon cloth (CP), Ni-PMDA precursor and Ni-BDC catalyst. Figure 8 In order to experimentally measure the urea and ammonia nitrogen Faraday efficiencies of the Ni-PMDA@Fe catalyst and compare the urea selectivity of several catalysts, the catalyst of the present invention achieved a maximum urea Faraday efficiency of 41.06% at -0.5V vs.RHE and effectively suppressed the formation of by-product ammonia nitrogen. The urea selectivity of the catalyst of the present invention was significantly higher than that of the Ni-PMDA precursor and the Ni-BDC catalyst. Fig. 9The double-layer capacitance of various catalysts was measured using the electrochemical CV method, which represents the size of the electrochemically active surface area (ECSA) of each catalyst. Among them, the Ni-PMDA@Fe catalyst obtained the highest double-layer capacitance, indicating the advantages of the catalyst of the present invention in catalytic kinetics.
[0044] In summary, the present invention patent designs a nickel-iron bimetallic organic polymer catalyst Ni-PMDA@Fe and applies it to the field of urea electrosynthesis, which has high urea yield and selectivity, kinetic advantages, and comprehensive performance better than Ni-PMDA precursor and common Ni-BDC catalyst. Therefore, this carbon cloth-supported nickel-iron bimetallic catalyst has good development and application prospects in the field of urea electrosynthesis.
Claims
1. A nickel-iron bimetallic organic polymer, characterized in that: The product is prepared with Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and pyromellitic dianhydride PMDA as raw materials, wherein Ni(NO3)3·6H2O and Fe(NO3)3·9H2O provide metal atoms, PMDA serves as anhydride ligand, and tetrahydrofuran THF and anhydrous ethanol are used as solvents.
2. A nickel-iron bimetallic organic polymer according to claim 1, characterized in that: Phthalic acid BDC was used instead of pyromellitic dianhydride PMDA.
3. The method for preparing a nickel-iron bimetallic organic polymer according to claim 1, characterized in that: Here is how: 1) Ni(NO3)2·6H2O solid and PMDA solid are dissolved in THF respectively to obtain a metal salt solution and a PMDA dispersion, the PMDA dispersion is added dropwise to the metal salt solution, the mixed solution is dispersed by ultrasound, transferred to a Teflon high-pressure reactor, placed in a blast drying oven for reaction for a specific time and cooled to room temperature, the reaction solution is filtered and the obtained solid is dried and ground to obtain a Ni-PMDA precursor; 2) Take Ni-PMDA precursor and Fe(NO3)3·9H2O solid, add anhydrous ethanol, stir for 12 hours to allow iron and Ni-PMDA precursor to form a polymer, transfer the stirred liquid to a centrifuge tube for centrifugation, repeat the centrifugation several times and wash, and transfer to a vacuum dryer to obtain Ni-PMDA@Fe solid.
4. The method for preparing a nickel-iron bimetallic organic polymer according to claim 2, characterized in that: In step 1), the molar ratio of Ni(NO3)2·6H2O solid to PMDA is 5:
2.
5. The method for preparing a nickel-iron bimetallic organic polymer according to claim 2, characterized in that: In step 1), the reaction temperature is 120° C., the reaction time is 48 h, and the mixture is naturally cooled to room temperature.
6. The method for preparing a nickel-iron bimetallic organic polymer according to claim 2, characterized in that: In step 3), the mass ratio of Ni-PMDA precursor:Fe(NO3)3·9H2O=1:
1.
7. A nickel-iron bimetallic organic polymer catalytic electrode, characterized in that: The nickel-iron bimetallic organic polymer described in claim 1 is mixed with acetylene black, DuPont membrane solution, isopropyl alcohol and ultrapure water to prepare ink, and the ink is dripped onto the carbon cloth using a syringe to obtain a catalytic electrode.
8. A nickel-iron bimetallic organic polymer catalytic electrode according to claim 7, characterized in that: Nickel-iron bimetallic organic polymer: acetylene black: DuPont membrane solution: isopropanol: ultrapure water = 3mg: 3mg: 30ul: 170ul: 200ul.
9. Use of the nickel-iron bimetallic organic polymer catalytic electrode according to claim 7 or 8 in electrochemical urea synthesis.
10. The use according to claim 9, wherein the nickel-iron bimetallic organic polymer catalytic electrode according to claim 7 or 8 is used as a working electrode, the counter electrode is a platinum sheet electrode, the reference electrode is an Ag / AgCl reference electrode, the cathode electrolyte is 35 ml each of 0.1M KNO3 solution and 0.1M KHCO3 solution, the anolyte is 70 ml of 0.1M KHCO3 solution, the electrolysis time is 2 hours at a single potential, and the cathode electrolyte product is collected.
Citation Information
Patent Citations
Nickel-based metal organic framework prepared based on solvothermal synthesis method as well as synthesis method and application of nickel-based metal organic framework
CN115975213A
Preparation method of Ni-PMDA electrode made of carbon cloth loaded Ni-based MOF material and application of Ni-PMDA electrode in electrochemical synthesis of urea
CN117512689A
Preparation method of Cu-based metal organic polymer material and application of Cu-based metal organic polymer material in electro-catalytic synthesis of urea
CN118206770A
Preparation method and application of iron-nickel nano-alloy / nano-porous carbon composite catalyst
CN118814203A
Robot safety evaluation method
KR102759672B1